Chronic intermittent hypoxia due to obstructive sleep apnea slightly alters nutritional status: a pre-clinical study - Breuillard, Charlotte; Moulin, Sophie; Bouyon, Sophie; Couchet, Morgane; Moinard, Christophe; Belaidi, Elise (Frontiers in Nutrition, 2023)
Obstructive sleep apnea syndrome (OSAS) is associated with chronic intermittent hypoxia (cIH) that causes disturbances in glucose and lipid metabolism. Animals exposed to cIH show lower body weight and food intake, but the protein-energy metabolism has never been investigated. Here, to address the gap, we studied the impact of cIH on nutritional status in rats. 24 male Wistar rats were randomized into 3 groups (n=8): a control group (Ctrl), a cIH group (cIH) exposed to cIH (30 sec 21%-30 sec 5% fraction of inspired oxygen, 8h per day, for 14 days), and a pair-fed group ("PF") exposed to normoxia with food intake adjusted to the intake of the cIH group rats with anorexia. Body weight and food intake were measured throughout the study. After 14 days, the rats were euthanized, the organs were collected, weighed, and the liver, intestine mucosa, and muscles were snap-frozen to measure total protein content. Food intake was decreased in the cIH group. Body weight was significantly lower in the cIH group only (-11%, p<0.05). Thymus and liver weight as well as EDL protein content tended to be lower in the cIH group than in the Ctrl and PF groups. Jejunum and ileum mucosa protein contents were lower in the cIH group compared to the PF group. cIH causes a slight impairment of nutritional status and immunity. This pre-clinical work argues for greater consideration of malnutrition in care for OSAS patients. Further studies are warranted to devise an adequate nutritional strategy.